Применение высокопрочного бейнитного чугуна для производства сменных деталей грунтообрабатывающей сельхозтехники - Волощенко, Сергей Михайлович; Гогаев, Казбек Александрович; Аскеров, Мукафат Гейбат оглы; Миропольский, Александр Михайлович (НТУ "ХПИ", 2017)
Проведен сравнительный анализ эксплуатации зарубежных и украинских сменных деталей почвообрабатывающей сельхозтехники. Ресурс работы отечественных деталей в несколько раз уступает ресурсу зарубежным образцам. Кроме того, импортные детали не подходят к навесному оборудованию техники, произведенной в Украине. Количество зарубежной сельхозтехники постоянно увеличивается, что требует увеличение поставок сменных деталей, стоимость которых в 5 – 8 раз превышает стоимость деталей украинского производства. В этой связи задача замены импортных деталей аналогичными деталями отечественного производства с высоким ресурсом работы, не уступающему ресурсу лучших образцов зарубежного производства, является весьма актуальной. В Институте проблем материаловедения НАНУ проведены работы по созданию технологии изготовления литых лемехов из высокопрочного бейнитного чугуна, обладающих ресурсом, сравнимым и превышающим с ресурсом лучших зарубежных образцов.

A comparative analysis of the exploitation of foreign and Ukrainian replaceable parts of soil-cultivating agricultural machinery is carried out. The resource of the work of domestic parts is several times less than the resource for foreign models. In addition, imported parts do not match the attachments of equipment produced in Ukraine. The number of foreign agricultural machinery is constantly increasing, which requires an increase in the supply of replacement parts, the cost of which is 5 – 8 times higher than the cost of parts produced in Ukraine. In this regard, the task of replacing imported parts with similar parts of domestic production with a high resource of work, not inferior to the resource of the best samples of foreign production, is very relevant. The Institute for Material Science Problems of the National Academy of Sciences of Ukraine has carried out work on the development of a technology for the production of cast plowshares from high-strength bainitic cast iron with a resource comparable and exceeding that of the best foreign samples. The purpose of this work is to develop a technology for the production of cast interchangeable parts in a high service life in replacement of existing serial steel samples. As a result of laboratory tests it was establ ished that cast replacement parts for soil-cultivating agricultural machinery when working in soils of different types have a service life of 2-5 times higher than serial steel plowshares.
Application of high-strength beauty iron for the production of replacement parts of grand-treatment agricultural machinery
Keywords: навесное оборудование; детали; оборудование; литой лемех; attached equipment; soil cultivating equipment